Role of nano-hydrogels coated exosomes in bone tissue repair - Pan, Yuqi; Li, Yige; Dong, Wenjun; Jiang, Bowei; Yu, Yuhao; Chen, Yunsu (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of nanotechnology, nanomaterials are widely applied in different areas. Some nanomaterials are designed to be biocompatible and can be used in the medical field, playing an important role in disease treatment. Exosomes are nanoscale vesicles with a diameter of 30–200 nm. Studies have shown that exosomes have the effect of angiogenesis, tissue (skin, tendon, cartilage, et al.) repair and reconstruction. Nano-hydrogels are hydrogels with a diameter of 200 nm or less and can be used as the carrier to transport the exosomes into the body. Some orthopedic diseases, such as bone defects and bone infections, are difficult to handle. The emergence of nano-hydrogels coated exosomes may provide a new idea to solve these problems, improving the prognosis of patients. This review summarizes the function of nano-hydrogels coated exosomes in bone tissue repair, intending to illustrate the potential use and application of nano-hydrogels coated exosomes in bone disease.